Between architecture and Digital Twin: the 3D survey of the Visconti Tower of the famous Monza Park (Archeomatica, 2023)
In collaboration with the Consorzio Villa Reale, the topographic, 3D and aerial photogrammetric surveys of the Visconti Tower of the Monza Park were carried out. The surveys were carried out to obtain an extremely detailed, precise and georeferenced 3D model of the building in order to produce high-level internal and external elevations and floor plans and to obtain a digital twin of the structure. The survey is the result of different survey tools and techniques integrated together.